Environmental Parameters And Phytoplankton Community Quality: Implications For Food Safety In Coastal Communities - Tambaru, Rahmadi (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2023)
This study aimed to evaluate environmental parameters and phytoplankton quality as well as the implications for the food safety of seafood-consuming coastal communities. The study was conducted in coastal waters of South Sulawesi, Indonesia at four sites (three stations/site): Pangkep (PK), Kuri (KR), Maros (MR), and Tallo (TL) during June, August, and October 2020. Observations formed three spatial clusters: MR1, PK; MR2, MR3, TL; KR (92.5 % similarity), and two temporal clusters: June 2020; August and October 2020 (87.9 % similarity). PCA showed parameters most strongly characterizing TL, KR, and MR (except MR1) were high levels of salinity, nitrate, nitrite, ammonium, silicate, temperature, pH, and abundance of both phytoplankton that can form harmful algal blooms (HABs) and non-HAB forming phytoplankton (non-HABs), with low current velocity. PK was characterized by high current velocity, non-HABs, orthophosphate, ammonium, nitrite, and turbidity with low nitrate and HABs. Main characterizing parameters in the temporal PCA were high current velocity and HABs with low orthophosphate in June 2020; high nitrate, ammonium, orthophosphate, and non-HABs with even lower HABs in August 2020; high turbidity, temperature, and salinity with low pH, nitrite, silicate, and HABs in October 2020. Current velocity (low at TL, KR, MR and high at PK) influenced both non-HABs and HABs. The results indicate that faster currents may have impeded HABs development so that the phytoplankton quality was still good. Therefore, the fish from these waters can be considered safe for human consumption, thereby contributing to maintaining the health of coastal communities.